Integration of radiology in the modular system at the undergraduate level - Ara, Iffat; Ali, Azmat; Khan, Shaukat Hayat; Bibi, Rashada; Akram, Fiaza; Khan, Laila (Journal of Ayub Medical College Abbottabad, 2021)
Background: Integration of Radiology is challenging because in the traditional system it is introduced with a clinical subject while in an integrated curriculum, vertical integration of Radiology is done with anatomy in the first year and with pathology, forensic medicine, ophthalmology, ENT, gynaecology surgery, and medicine till the final year. This study was done with the purpose to evaluate Radiology teaching in an integrated curriculum in undergraduate students of Azad Jammu Kashmir medical college/Sheikh Khalifa Bin Zaid Hospital Muzaffarabad. Method: This study was done to determine student's perceptions regarding Radiology teaching at Azad Jammu Kashmir Medical College (AJKMC), starting from the foundation module of the first year till the final year. It was a descriptive cross-sectional type conducted in the Radiology department of AJKMC. The study duration was six months. Students of final year and recent graduates were included in the study. All the information was collected on pro forma. Pro forma included 11 structured, close-ended, quantitative types of questions. Five points Likert scale was given starting from strongly agree to strongly disagree. Data was analysed by descriptive statistics. Results: In 100 students who gave feedback, the age range was from 23 to 26 year. Male students were 32 (32%) and female 68(68 %). 70% of students agreed and 14% strongly agreed for the integration of Radiology at the undergraduate level. Six percent students disagreed with the integration of radiology at the undergraduate level. Conclusion: Integration of Radiology in a modular system for undergraduate students at AJKMC was supported by the majority of participants. Keywords: Radiology; Integrated curriculum; Undergraduates; Modular System